2009
DOI: 10.1088/0031-9155/54/3/013
|View full text |Cite
|
Sign up to set email alerts
|

Computerized method for estimation of the location of a lung tumor on EPID cine images without implanted markers in stereotactic body radiotherapy

Abstract: The purpose of this study was to develop a computerized method for estimation of the location of a lung tumor in cine images on an electronic portal imaging device (EPID) without implanted markers during stereotactic body radiotherapy (SBRT). Each tumor region was segmented in the first EPID cine image, i.e., reference portal image, based on a multiple-gray level thresholding technique and a region growing technique, and then the image including the tumor region was cropped as a 'tumor template' image. The tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 16 publications
0
42
0
Order By: Relevance
“…However, the approach of markerless tumor tracking in EPID movies could be improved with the help of external motion signals (5), with further image processing of the EPID movies to improve the signal-to-noise-contrast, or based on machine learning algorithms (4,17). Tang et al recently published a method to decide if the tumor is either inside or outside the beam aperture based on neural networks (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the approach of markerless tumor tracking in EPID movies could be improved with the help of external motion signals (5), with further image processing of the EPID movies to improve the signal-to-noise-contrast, or based on machine learning algorithms (4,17). Tang et al recently published a method to decide if the tumor is either inside or outside the beam aperture based on neural networks (17).…”
Section: Discussionmentioning
confidence: 99%
“…Precise assessment and quantification of breathinginduced target motion and its integration into the treatment workflow are essential for adaptive treatment techniques (1). Existing strategies for tumor tracking approaches can be grouped roughly into three categories: external surrogate based (2,3), markerless (4)(5)(6), and internal marker-based systems (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…The contrast value was calculated as follows: Contrast=InormalwInormalbIw, where I w and I b were the average intensities within a 10 × 10 square pixels inside a white rectangular and a black rectangular, respectively, between two numbers ‘1’ and ‘2’ of the phantom image (Fig. 1(a)) 26. The signal‐to‐noise ratio (SNR) was evaluated using the following formula: SNR=Iwσb, where I w was the same as above, and the σ b was the standard deviation inside the same black box also mentioned above.…”
Section: Methodsmentioning
confidence: 99%
“…Markerless tumor tracking, by means of both kV and MV imaging, is a research area receiving increasing attention in recent years. Studies such as those conducted by Meyer et al, 18 Arimura et al, 19 and more recently by Rottmann et al 20 have demonstrated the feasibility and more favorable advantages of markerless EPID tracking compared to implant-based kV tracking approaches, although these have not yet been applied to RGRT. In this work, the suitability and potential of an in-house clinical tool for markerless position verification of lung tumors during RGRT is investigated.…”
Section: Introductionmentioning
confidence: 99%